2016
DOI: 10.1902/jop.2016.150636
|View full text |Cite
|
Sign up to set email alerts
|

Cone‐Beam Computed Tomography for Detection of Intrabony and Furcation Defects: A Systematic Review Based on a Hierarchical Model for Diagnostic Efficacy

Abstract: From the assessed studies, it can be concluded that there is not sufficient scientific evidence to justify the use of CBCT for the diagnosis of and/or treatment planning for intrabony and furcation defects. Furthermore, the effectiveness of CBCT for such diagnostic tasks has been assessed only at low diagnostic efficacy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 58 publications
(171 reference statements)
2
32
1
1
Order By: Relevance
“…Thus, there is no evidence to support routine use of CBCT to detect interproximal defects as a preventive measure. Our results are in agreement with the guidelines of the Swiss Society of Dentomaxillofacial Radiology [29] and with a recent systematic review [32]. …”
Section: Discussionsupporting
confidence: 92%
“…Thus, there is no evidence to support routine use of CBCT to detect interproximal defects as a preventive measure. Our results are in agreement with the guidelines of the Swiss Society of Dentomaxillofacial Radiology [29] and with a recent systematic review [32]. …”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review discussed the lack of CBCT standard exposure parameters (FOV and voxel size) for diagnosis of bone defects related to periodontitis 31 . The authors of the review concluded that there is not sufficient scientific evidence to support the use of CBCT for the diagnosis and/or treatment planning of intrabony and furcation defects 31 . Moreover patient desires and requests are also relevant, along with the technical and financial effort involved 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the review concluded that there is not sufficient scientific evidence to support the use of CBCT for the diagnosis and/or treatment planning of intrabony and furcation defects 31 . Moreover patient desires and requests are also relevant, along with the technical and financial effort involved 31 . Also the additional radiation risk of the CBCT examination should be justified in patients for whom clinical measures and conventional radiographs cannot provide sufficient treatment information 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kontrolateral kemik ve dental yapıların superpozisyonları iki boyutlu radyograflarla görüntülenemez (33,34). Literatür bilgileri, KIBT'nin bu kemik defektlerinin de tanımlanması ve ölçülmesindeki doğruluğunu kanıtlamıştır (35,32).…”
Section: Periodontolojide Kullanımıunclassified